Grachi prileteli - Savrasov, Alexei Kondratyevich (Академия художеств СССР (Academy of Arts of the USSR), 1953)
Artwork; rook birds swarming winter trees 1953 reproduction of 1871 painting 'The rooks have arrived' by A. Savrasov. Original title: Грачи прилетели PO-0923